Performance Management and Quality Assurance in Higher Education: A Conceptual Framework for a Blended Approach - Rashidi, Elias; Jingura, Raphael M. (International Journal of African Higher Education, 2024)
This article proposes a framework to promote continuous quality improvement in higher education by bringing performance management and quality assurance together in a single approach. Blending the two systems eliminates the challenges of a two system approach. The study employed a quantitative methodology, with data collected by means of a closed-ended questionnaire administered to academic and administrative staff at four purposely selected public higher education institutions in Zimbabwe’s four major ethnic regions. The questionnaire drew insights from a framework developed by Silimperi et al. (2002) on essential elements for developing quality assurance systems. Fourteen elements were used to determine the possibility of blending the two systems. Of these, nine had a mean score of 4.0, three above 3.5 and two had a mean score of less than 3.5. These results indicate a high likelihood that the systems can be blended.